Analysis Of Power Requirements and Solar Power Plant (PV System) Components For an Electric Vehicle Charging Station at Universitas Pembangunan Panca Budi Medan - Hamdani Ahmad Rangkuti; Dicky Lesmana; Haris Gunawan (Sean Institute, 2025)
This study focuses on determining the capacity of the solar power plant (PLTS) components used as an energy source at a public electric vehicle charging station (SPKLU) to charge the batteries of electric cars at Universitas Pembangunan Panca Budi Medan. Calculations are carried out to obtain the area of the solar module, the power required, the number of solar panels, the SCC capacity, the backup battery, and the charging time of the electric vehicle. The research method used is a research method with an approach calculation by comparing several similar references related to planning in building a PLTS. The battery data collection method is carried out by observation, literature study and collection of weather condition data through the BMKG of Medan City. The results of the study show that with a solar intensity of Gav 4.42 kWh/m2/day, a module array area of 42,071 m2 is required. With a sunlight intensity of 1000 W/m2, the power generated by the area is 6,731 Wp. By using a 120 WP solar module, the number of panels used is 60 units consisting of 15 strings of 4 units in each string. The system can produce 8,333 Wp, 71 V 103 A of power. The SCC produces 128.73 A. The charging time required is 8.63 hours or 8 hours 37 minutes.